Nonlinear Numerical and Analytical Assessment of the Shear Strength of RC and SFRC Beams Externally Strengthened with CFRP Sheets - Sabiha Barour; Abdesselam Zergua; Farid Bouziadi; Mosbeh R. Kaloop; Waleed E. El-Demerdash (Advances in Civil Engineering)
This study investigates numerically utilizing nonlinear finite element (ANSYS software) and analytically the shear response of the Reinforced Concrete (RC) beams. Different beams are considered in the current study, such as RC, steel fibre reinforced concrete (SFRC) without web reinforcement, and RC externally reinforced in the shear zone with carbon fibre reinforced polymer (CFRP) sheets. Nonlinear finite element model (FEM) is designed to simulate the performance of the designed beams. The results of FEM are compared to experimental measurements and standard design codes (ACI 440.2R-17, FIB 14, CNR-DT200, and ACI 318-19). According to the experimental approach and nonlinear finite element, the enhancement in the load carrying capacity of SFRC beam due to CFRP strengthening decreases with a volume fraction of steel fibres of 2%. However, the effect of CFRP strengthening on the shear behaviour of RC beams was observed in increased load carrying and ultimate deflection capacities as a result of the CFRP strengthening. The results show that CFRP has a significant contribution to shear strength. At each load increment, the created model accurately reproduced the initial and progressive crack patterns. A comparison of nonlinear finite element and analytical models was conducted using the codes ACI 440.2R-17, FIB 14, CNR-DT200, and ACI 318-19. Numerically, the FEM results showed a high agreement with ACI 440.2R-17 standard code, with correlation approach to 99%. The comparison experimental load capacity of beams to FEM and ACI 440.2R-17 shows that the FEM can be significantly used to estimate the shear strength of beams in the X-Y directions with simulating different scenarios of CFRP and SFRC characteristics. The discrepancy between the nonlinear FEA and the theoretical predictions from the ACI 440.2R-17 code is less than 1%, from the FIB14 code is less than 2%, from the CNR-DT200 code is less than 15%, and from the ACI 318-19 code is less than 30%. The ultimate load capacity evaluated based on ACI 440.2R-17 code provision shows a good agreement with the experimental data as compared to the others’ code provision. The results of the finite element analysis and analytical models were in good agreement with the experimental results. The most significant advantage of finite element analysis over experimental approaches was that it can aid in the investigation of different output results that cannot be measured experimentally, such as shear stress in the XY direction throughout the beam strengthened in shear with different CFRP properties and steel fibre reinforced concrete (SFRC).